2020
DOI: 10.3390/nano11010036
|View full text |Cite
|
Sign up to set email alerts
|

Prunus spinosa Extract Loaded in Biomimetic Nanoparticles Evokes In Vitro Anti-Inflammatory and Wound Healing Activities

Abstract: Prunus spinosa fruits (PSF) contain different phenolic compounds showing antioxidant and anti-inflammatory activities. Innovative drug delivery systems such as biomimetic nanoparticles could improve the activity of PSF extract by promoting (i) the protection of payload into the lipidic bilayer, (ii) increased accumulation to the diseased tissue due to specific targeting properties, (iii) improved biocompatibility, (iv) low toxicity and increased bioavailability. Using membrane proteins extracted from human mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
2
21
1
1
Order By: Relevance
“…Recently, we have reported that polyphenols of P. spinosa flowers are able to effectively scavenge several other in vivo-relevant ROS, such as O 2 •− , ONOO − , HO • and HClO [ 41 ]. On the other hand, Sabatini et al [ 24 ] and Tiboni et al [ 25 ] have demonstrated that the ethanol extracts from sloes decrease the expression of interleukin-1 receptor-associated kinase (IRAK-1) in stimulated U937 cells, which plays a crucial role in regulating signalling cascades and NF-κB activation. In the present study, we observed that the sloe extracts significantly diminished the release of TNF- α from both neutrophils and PBMCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported that polyphenols of P. spinosa flowers are able to effectively scavenge several other in vivo-relevant ROS, such as O 2 •− , ONOO − , HO • and HClO [ 41 ]. On the other hand, Sabatini et al [ 24 ] and Tiboni et al [ 25 ] have demonstrated that the ethanol extracts from sloes decrease the expression of interleukin-1 receptor-associated kinase (IRAK-1) in stimulated U937 cells, which plays a crucial role in regulating signalling cascades and NF-κB activation. In the present study, we observed that the sloe extracts significantly diminished the release of TNF- α from both neutrophils and PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The previous research on the biological activity of P. spinosa fruits has focused mainly on their antioxidant potential [ 11 , 14 , 21 , 22 ], with some data available on the antidiabetic, antimicrobial, anti-inflammatory and anticancer activity [ 15 , 17 , 23 , 24 , 25 ]. The accumulated results suggest the high value of blackthorn fruits as health-promoting food and source material for the production of functional supplements, but further research is required to characterise the underlying mechanisms, which might be relevant to their in vivo effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent article cited the use of Prunus spinosa fruits (PSF) containing different phenolic compounds as biomimetic nanoparticles that could improve the activity of the extract where the payload is directed into the lipid bilayer with increased accumulation at the diseased tissue (showing enhanced specific targeting properties). Improved biocompatibility, as well as a low toxicity, was observed when the nanoparticle was evaluated on HUVEC cells suggesting a unique platform for encapsulation of drugs that have minimal stability and bioavailability [110].…”
Section: Overcoming Biological Barriers Along With Increased Bioavailabilitymentioning
confidence: 99%
“…To improve biocompatibility and increase tissue accumulation, Prunus spinosa extract has also been loaded into biomimetic nanoparticles. These formulations have been shown to have a greater anti-inflammatory, antioxidant activities and a more wound-healing effect compared to free formulation [ 63 ].…”
Section: Experimental Evidence Of Dual Antioxidant or Pro-oxidant Effect Of Prunus Spinosa Extract On Colorectal Cancementioning
confidence: 99%